Women, politics and the public sphere - Brooks, Ann, 1952- (Bristol, UK ; Chicago, IL, USA : Policy Press, 2019)
Women, Politics and the Public Spherefocuses intellectually on the legacy of eighteenth-century women thinkers, writers and political philosophers in understanding the emergence of women public intellectuals in the US and UK, and highlights how women public intellectuals now reflect much more social and cultural diversity.
The gender politics of 'bluestocking philosophy' -- Gender and the politics of the public sphere -- 'Uncompromising politics': Mary Wollstonecraft and Catherine Macaulay -- Women writers: setting the terms of the debate -- The role of social movements leading to the emergence of women public intellectuals -- Contemporary women public intellectuals: the United states (1) -- Contemporary women public intellectuals: the United States (2).
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Women political activists; Women -- Political activity -- History; Women philosophers -- History; Women intellectuals -- History